Relación entre las prácticas de alimentación y su efecto sobre la calidad del agua en estanques de piscicultura (monografía). (2021)
In this monograph a bibliographic review is carried out in order to acquire updated knowledge on the relationship between feeding practices and their impact on environmental quality in fish farming ponds, collecting information on different species of fish in production, in order to identify Aspects to take into account for a good diet with the least impact on the general state of the water.